Strategies for Managing Technological Change: Insights from Practitioners - Blair, Garry; Pagano, Rosane (Journal of Productive Discourse, 2023)
Technology is vital to most organisations and, hence, the ability to change this element is essential for their future success. Change will contribute to the fulfilment of customer or service user needs, via enhancement of the technological basis for these entities. An efficient and effective delivery of organisational objectives can depend on this ability to achieve successful technological change. This paper examines the change process for technology, considering the techniques for delivering change and the types of change in this sphere. The objective is to obtain an enhanced understanding of how technology can be amended in organisations and also consider the types of change identified by managers. The latter will inform the range of techniques that are recommended for use with the breadth of technologies, existing in organisations. The paper, thus, addresses this critical activity and offers insights into the practice of technology management, formulating recommendations for practice and providing a contribution to academic theory in this subject area. A review of the literature was undertaken, in order to establish the key themes in this area. An empirical study was also enacted, in the form of a survey of a sample of UK-based, current practitioners. The requirements for technological change were obtained from these managers. The data from the literature and empirical study was examined via thematic analysis. The principal themes were discerned using a grounded approach. A framework, comprising a model of the required change, was then constructed to contribute to practice and academic theory, as well as summarise this research.